The importance of interpersonal communication in teaching modern students - Lehrer Kanfo , Orit (Biuletyn Socjoterapeutyczny, 2025)
The article focuses on the importance of interpersonal communication in lecturer-student relationships, in an era in which higher education has shifted from an elitist model to mass education. Through training and professional development, lecturers can improve their abilities in five key communication dimensions: lesson organization, message clarity, interaction with students, generating interest, and creating value. The combination of these dimensions, along with a learner-centred teaching approach and the adaptation of teaching practices to the unique characteristics of students from Generation Y and Z, are the key to quality teaching in higher education.